Editing of an Alpha-Kafirin Gene Family Increases, Digestibility and Protein Quality in Sorghum. Issue 4 (20th June 2018) - Li, Aixia; Jia, Shangang; Yobi, Abou; Ge, Zhengxiang; Sato, Shirley J.; Zhang, Chi; Angelovici, Ruthie; Clemente, Thomas E.; Holding, David R.
Abstract : Single-consensus guide RNA partially reduces kafirin levels in Sorghum bicolor grain, leading to an increased proportion of non-kafirins and improved digestibility and protein quality. Abstract: Kafirins are the major storage proteins in sorghum ( Sorghum bicolor ) grains and form protein bodies with poor digestibility. Since kafirins are devoid of the essential amino acid lysine, they also impart poor protein quality to the kernel. The α-kafirins, which make up most of the total kafirins, are largely encoded by the k1C family of highly similar genes. We used a clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) gene editing approach to target the k1C genes to create variants with reduced kafirin levels and improved protein quality and digestibility. A single guide RNA was designed to introduce mutations in a conserved region encoding the endoplasmic reticulum signal peptide of α-kafirins. Sequencing of kafirin PCR products revealed extensive edits in 25 of 26 events in one or multiple k1C family members. T1 and T2 seeds showed reduced α-kafirin levels, and selected T2 events showed significantly increased grain protein digestibility and lysine content. Thus, a single consensus single guide RNA carrying target sequence mismatches is sufficient for extensive editing of all k1C genes. The resulting quality improvements can be deployed rapidly for breeding and the generation of transgene-free, improved cultivars of sorghum, a major crop worldwide.